A study on customer's level of satisfaction towards Pos Malaysia Berhad (PMB) Kota Kinabalu counter service / Noor Astuti Judin - Judin, Noor Astuti (2009)
This project paper of marketing research is about customer's level of satisfaction towards Pos Malaysia Berhad (PMB) Kota Kinabalu counter service. This research is conducted to study and investigate what is the actual level of customer satisfaction towards the services provided at PMB Kota Kinabalu counter which include (i) identifying customer's preferences of services provided by Pos Malaysia Berhad (PMB) Kota Kinabalu at counter service, (ii) determining the customers' satisfaction towards PMB Kota Kinabalu Counter Services and (iii) identify customers' complaints and provide recommendations for improving the PMB Kota Kinabalu services. To find out those customers' satisfaction level, 100 respondents are needed to give feedback towards their preferences and liking through questionnaire and interviews.